Profitability, Firm Size, and Capital Structure: Implications for Firm Value in Food & Beverages Manufacturing - Zahrina Nilamsari; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2022)
This study examines the relationship between profitability, firm size, capital structure, and firm value in the Food & Beverages Manufacturing sector over the period 2016-2020. Purposive sampling was used to select a sample of eight companies, and secondary data from the Stock Exchange Gallery at Muhammadiyah University of Sidoarjo were analyzed using the path analysis technique and SmartPLS software. The findings reveal that profitability positively and significantly influences capital structure, while firm size has a negative and insignificant impact. Additionally, profitability has a positive and significant effect on firm value, while firm size has a negative and insignificant influence. Furthermore, firm size positively affects firm value. Notably, profitability has a positive and significant effect on firm value, mediated by capital structure, whereas firm size has a negative and insignificant effect on firm value through capital structure mediation. These findings contribute to the understanding of the factors shaping firm value in the Food & Beverages Manufacturing industry and offer implications for practitioners and policymakers seeking to optimize capital structure decisions and enhance firm performance. Highlights: Profitability positively influences capital structure in the Food & Beverages Manufacturing industry. Firm size does not significantly impact capital structure in the sector. Profitability has a significant positive effect on firm value, while firm size has a negligible impact. Keywords: Profitability, Firm Size, Capital Structure, Firm Value, Food & Beverages Manufacturing.